Social phenomenology : Husserl, intersubjectivity, and collective intentionality - Chelstrom, Eric (Lexington Books, 2013)
Social Phenomenology offers an account of collective intentionality informed by the tradition of Husserlian phenomenology. The account argues that if consciousness and intentionality are only intrinsic to individuals, denying collectivism, that it does not follow that one endorses an atomistic conception of the subject.